Single-test parallel assessment of multiple genetic disorders. (May 2011) - Tavares, Purificação; Dias, Luís; Palmeiro, Aida; Rendeiro, Paula; Tolias, Peter
We advocate a new paradigm for genetic diagnosis based on using customized array panels, each of which groups multiple genes and mutations associated with clinical profiles that are common to particular syndromic diseases. This parallel approach, based on a single-test multigene multiplexing strategy, compared with traditional sequential testing by gene-by-gene genetic analysis, drastically reduces the time and cost of diagnosis while maintaining accuracy and reliability. Faster diagnosis enables early decision-making to facilitate better patient management and outcomes at reduced costs to the healthcare system.